2009
DOI: 10.1177/0218492309348948
|View full text |Cite
|
Sign up to set email alerts
|

Figure-of-Eight vs. Interrupted Sternal Wire Closure of Median Sternotomy

Abstract: Sternal dehiscence is a rare but devastating complication following median sternotomy for cardiac surgery. The optimal technique for sternal closure is unclear. We conducted this prospective randomized trial to compare the incidence of sternal dehiscence after figure-of-8 and simple interrupted suturing in patients undergoing coronary artery bypass grafting. Between January 2007 and June 2008, 98 patients had figure-of-8 suturing and 97 had interrupted sutures. The mean age of the patients was 60.9 +/- 7.6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
3
24
0
1
Order By: Relevance
“…Ramzisham et al suggested that figure-of-eight sternal closure is equally effective as simple wire suturing in preventing adverse outcomes of sternal dehiscence. 10 Vular et al showed that sternal closure reinforced with rib heads technique is extremely efficient and twenty-two patients from twentythree ones whom were treated with this technique survived 11 while our study showed that figure-eight and simple technique are more related to the risk of morbidity and mortality. 11 Not accessing of association between bone healing and pain scores or complications, and not analyzing of the effect of pain severity on the activity or quality of life were limitations of our study.…”
Section: Discussionsupporting
confidence: 45%
“…Ramzisham et al suggested that figure-of-eight sternal closure is equally effective as simple wire suturing in preventing adverse outcomes of sternal dehiscence. 10 Vular et al showed that sternal closure reinforced with rib heads technique is extremely efficient and twenty-two patients from twentythree ones whom were treated with this technique survived 11 while our study showed that figure-eight and simple technique are more related to the risk of morbidity and mortality. 11 Not accessing of association between bone healing and pain scores or complications, and not analyzing of the effect of pain severity on the activity or quality of life were limitations of our study.…”
Section: Discussionsupporting
confidence: 45%
“…In human beings, median sternotomy is associated with a complication rate of 0·3 to 5% of cases and instability, non‐union and infection are common complications (Kreitmann and others 1992, Cohen and Griffin 2002, Luciani and others 2006, Ramzisham and others 2009). The use of polydioxanone has recently been validated as an alternative to wires in selected patients (infants and patients with body surface area <1·5 m 2 ) to prevent poststernotomy dehiscence (Keceligil and others 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Most authors agree that the most important one is sternal stability after closure. 9,13,14,21 While many studies were performed to compare sternal closure methods, till now there is no ultimate method that gained the full support from all surgeons. In present study, authors compared two techniques and concluded that, regarding sternal stability, the multi-twist sternal closure showed better results than figure of eight technique despite the difference between both methods was not statistically significant mainly due to small number of patients involved in the study.…”
Section: Discussionmentioning
confidence: 99%